EVALUASI KOMPREHENSIF PROGRAM PEMBINAAN PRESTASI OLAHRAGA TAEKWONDO MAHAMERU INDONESIA MENGGUNAKAN MODEL CONTEXT, INPUT, PROCESS, DAN PRODUCT (CIPP) - Fadlilah, Nurul; Gatot Jariono; Nurhidayat Nurhidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the implementation of the Taekwondo training program using the Context, Input, Process, and Product (CIPP) evaluation model. The research employed a qualitative approach with an evaluative method. The research subjects included coaches, organizational administrators, and Taekwondo athletes involved in the training program. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that in the context aspect, the Taekwondo training program was implemented to meet the needs of developing sports skills, discipline, and athlete achievement, indicating that the program objectives are relevant to the participants' needs. In the input aspect, the availability of coaches, participants, and organizational support was considered adequate, although some limitations in training facilities and infrastructure were still found. In the process aspect, the training activities were carried out through regular practice sessions, learning of basic and advanced techniques, and periodic evaluation of athletes’ abilities. In the product aspect, the program was able to improve technical skills, discipline, and athletes’ achievements in both training and competitions. Overall, the evaluation results show that the Taekwondo training program has been implemented quite well and has the potential to be further developed through improved training management, better facilities, and continuous development of athlete training strategies.